Swirling Fluid Reduces the Bounce of Partially Filled Containers - Gordillo-Zavaleta, L (American Physical Society, 2023)
Certain spatial distributions of water inside partially filled containers can significantly reduce the bounce of the container. In experiments with containers filled to a volume fraction φ, we show that rotation offers control and high efficiency in setting such distributions and, consequently, in altering bounce markedly. High-speed imaging evidences the physics of the phenomenon and reveals a rich sequence of fluid-dynamics processes, which we translate into a model that captures our overall experimental findings. © 2023 authors. Published by the American Physical Society.